Electric Differential With Svpwm Direct Torque Control Using Five-Leg Inverter For Electric Vehicles - Ibrahim, Zulkifilie; Mohd Yaakop, Nurazlin; Sulaiman , Marizan; Mat Lazi, Jurifa; Abu Hasim, Ahmad Shukri; Patakor, Fizatul Aini (Little Lion Scientific Islamabad Pakistan, 2012)
-